2022
DOI: 10.1155/2022/1146186
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PTCD1 in Bladder Urothelial Carcinoma Predicts Poor Prognosis and Levels of Immune Infiltration

Abstract: Pentatricopeptide repeat domain 1 (PTCD1) was reported to regulate mitochondrial metabolism and oxidative phosphorylation. However, the effect and mechanism of PTCD1 in the development of bladder urothelial carcinoma (BLCA) remain unclear. The databases from The Cancer Genome Atlas (TCGA) and Human Protein Atlas (HPA) were used to analyze the expression changes, clinical features, and prognostic values of PTCD1. A nomogram was built to predict the prognostic outcomes of BLCA cases. The potential genes interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Some studies have found that POLR2J is overexpressed in rectal tumor organoids 20 . In addition, POLR2J is strongly positively correlated with pentapeptide-repeat domain 1 ( PTCD1 ) 21 , a mitochondrial matrix protein containing eight PPR domains 22 that regulate mitochondrial metabolism and oxidative phosphorylation. PTCD1 may be involved in immune function and immune cell infiltration, and may play a role in tumor progression and metastasis 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that POLR2J is overexpressed in rectal tumor organoids 20 . In addition, POLR2J is strongly positively correlated with pentapeptide-repeat domain 1 ( PTCD1 ) 21 , a mitochondrial matrix protein containing eight PPR domains 22 that regulate mitochondrial metabolism and oxidative phosphorylation. PTCD1 may be involved in immune function and immune cell infiltration, and may play a role in tumor progression and metastasis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, POLR2J is strongly positively correlated with pentapeptide-repeat domain 1 ( PTCD1 ) 21 , a mitochondrial matrix protein containing eight PPR domains 22 that regulate mitochondrial metabolism and oxidative phosphorylation. PTCD1 may be involved in immune function and immune cell infiltration, and may play a role in tumor progression and metastasis 21 . Cancer elicits an immune response that solid tumors can evade, in part by establishing an immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted according to the method of Dr. Zhou et al [ 21 ]. The TCGA database was used to collect clinical data (containing 539 KIRC cases), including gender, age, grade, TNM stage, pathological stage, survival status, and survival time.…”
Section: Methodsmentioning
confidence: 99%